NEW TECHNIQUE TO EVALUATE THE OVERALL HEAT LOSS COEFFICIENT FOR A FLAT PLATE SOLAR COLLECTOR - Amor Bouhdjar; Hakim Semai; Aissa Amari (Journal of Energy Technology, 2023)
Low-temperature solar systems mostly use flat plate solar collectors. Good design and correct di-mensioning of a solar heat generator are based on precise knowledge of the characteristics of the flat plate solar collector on site. The present work considers a flat plate solar air collector, a flat plate solar water collector, and a flat plate solar water collector with air absorber cooling. The investiga-tion intends to shed light on a procedure to determine the overall heat loss coefficient and the heat removal factor using recorded system temperatures, operating parameters, and environmental data. The Hottel-Whillier-Bliss equation gives the collector useful energy. This expression is used to gener-ate a correlation for the collector efficiency through a linear fitting. We calculate the overall heat loss coefficient of the collector from the slope of the collector efficiency curve. However, we need to know the heat removal factor of the collector. In this study, we present a new technique to calculate the heat removal factor. Then we deduce the collector overall heat loss coefficient. Results show that, very often, the overall heat loss coefficient for the flat plate solar air collector and the flat plate solar water collector determined with this new method is higher than the one calculated with the empirical formula proposed by Klein.